THE INDIAN SUMMER MONSOON CONTRIBUTION TO THE JJA RAINFALL OVER THE NOTERN PART OF SUMATRA DURING THE CO-OCCURING EL NINO AND DIPOLE MODE (+) YEARS - Sri Woro B.Harijono (International Journal of Remote Sensing and Earth Sciences (IJReSES), 2007)
This article describes the further study investigating the JJA rainfall formation in the northern part of Sumatra during the co-occuring El Nino and Dipole Mode (+) years. Analyses based on wavelet transformation reveal that the rainfall in that part of Sumatra is insensitive or at least insignificantly influenced by El Nino and or DM. This study confirms also that the Indian Summer Monsoon (IM) may play important roles in the rainfall budget of the region including in compensating the possible reduction effects of both El Nino and DM on the JJA rainfall. The characteristics of JJA rainfall over the northern part of Sumatra on a wavelet time-frequency plane are descreibed, and the relative contributions of EN-DM-Indian summer monsoon in the rainfall over the nothern part of Sumatra are demonstrated by using multicoliner statistical analysis. Keywords: Indian Summer Monsoon, Rainfall, El Nino, Dipole Mode.